Comparative analysis of methods for compiling the income statement: https://doi.org/10.5937/etp2404148V - Vladimirović, Ivana (Ekonomija - teorija i praksa, 2025)
Methods for compiling an income statement involve procedures for determining data on income and expenses for various purposes, such as calculating business results, periodic planning and control, decision-making, pricing, and more. For a company, accurate allocation of total costs is critically important. This requires breaking down the entire business process into specific organizational units or segments, providing a solid foundation for cost distribution across those parts. When expenses in the income statement are considered as a whole to assess business performance, the statement is compiled using the total cost method. In contrast, when the income statement is broken down to classify costs based on their contribution to value creation, grouped by functional areas, and distributed across shorter time periods, functions, tasks, processes, products, etc., it is compiled using the cost of goods sold method. The aim of this paper is to highlight the specific characteristics of the aforementioned methods and to present the advantages and disadvantages of their application through a comparative analysis.